Daily breathing inconsistency in pancreas SBRT: a 4DCT study - Sarkar, Vikren (J Gastrointest Oncol, 2018)
BACKGROUND: Stereotactic body radiation therapy (SBRT) treatments of pancreatic cancer typically employ relatively small margins. This study characterizes the motion of high visibility structures in close proximity to the pancreas to determine how much the motion envelope of such a structure changes due to respiratory variation between fractions. METHODS: Fanbeam, four-dimensional computed tomography (4DCT) studies acquired initially for planning and again prior to each treatment for 6 patients were used to fully characterize the change in motion of high-contrast structures in close proximity to the pancreas. RESULTS: Three of the six patients investigated had structures that showed a change in motion over the course of treatment that would not have been covered when using the typical 3 mm planning target volume (PTV) margins. For most of these large changes in motion envelope, a 4 mm uniform PTV margin would have allowed for coverage of the tumor. CONCLUSIONS: Half of the patients showed a change in motion envelope greater than would be covered by the commonly used PTV margins in pancreas SBRT. This shows that the impact of small margins must be very carefully considered during the planning process.